Vertical Distribution Patterns of Cephalopods in the Northern Gulf of Mexico - Judkins, Heather; Vecchione, Michael (Frontiers in Marine Science, 2020)
Cephalopods are important in midwater ecosystems of the Gulf of Mexico (GOM) as both predator and prey. Vertical distribution and migration patterns (both diel and ontogenic) are not known for the majority of deep-water cephalopods. These varying patterns are of interest as they have the potential to contribute to the movement of large amounts of nutrients and contaminants through the water column during diel migrations. This can be of particular importance if the migration traverses a discrete layer with particular properties, as happened with the deep-water oil plume located between 1000-1400 m during the Deepwater Horizon oil spill. Two recent studies focusing on the deep water column of the GOM (2011 Offshore Nekton Sampling and Analysis Program (ONSAP) and 2015-2018 Deep Pelagic Nekton Dynamics of the Gulf of Mexico (DEEPEND) program, produced a combined dataset of over 12,500 midwater-cephalopod records for the northern GOM region. We summarize vertical distribution patterns of cephalopods from the cruises that utilized a 10 m2 Multiple Opening/Closing Net and Environmental Sensing System (MOC10). About 95% of the cephalopods analyzed here either move through or live within 1000-1400 m zone. Species accounts include those with synchronous (e.g. Pterygioteuthis sp.) and asynchronous (e.g. Stigmatoteuthis arcturi) vertical migration. Non-migration patterns of some midwater cephalopods (e.g. Vampyroteuthis infernalis) are also highlighted. Ontogenic shifts are noted for some species examined.